APLIKASI FUMIGAN GAS FOSFIN (HIDROGEN FOSFIDA (PH3)) UNTUK PENGENDALIAN TIKUS (RODENT) - Ahmad Faisal; Martini Martini; Retno Hestiningsih; M Arie Wuryanto (Vektora : Jurnal Vektor dan Reservoir Penyakit, 2019)
Rats are widely distributed disease spreaders and settlement pests. Species of rats often found include Rattus norvegicus, R. tanezumi and Mus musculus. Phosphine as a fumigant is commonly used to control pests with no residue, especially related where there are placed the commercial products . The research objective was to determine effect of phosphine gas fumigant (hydrogen phosphide (PH3)) on rat death. The study sample was species of rats, i.e. M.musculus, R.tanezumi, and R.norvegicus. This study was used 4 dose variations (0, 4, 6 and 8 tablets) with 6 replications per unit treatment. Each treatment (dosis) needed 1 rat . The results of different test analyzed that significance value was 0.0001 (p=0.0001), indicating that there were differences in average time span of M. musculus, R. tanezumi and R. norvegicus death to treat of phosphine dose variations. Based on Probit analysis, the data showed that The fastest LT50 and LT99 were at a dose of 8 tablets for 90.5 and 114.9 minutes, and LT50 and LT99 were at the lowest dose of 4 tablets in 148.1 and 188.1 minutes, respectively. The higher dosage of phosphine was treated, the higher gas concentration was produced, so that it could kill M. musculus, R. tanezumi dan R. norvegicus quickly. The mortality might be generated by cell damages that occurred inside the body of rats.